FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PROSES BELAJAR DAN TINGKAT KECAKAPAN HIDUP REMAJA (Kasus Pengrajin Sandal Desa Cikaret Kecamatan Bogor Selatan) - Miskat Ramdhani; Sumardjo Sumardjo (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
The objectives of this research were: (1) to study the relationship between learning process, adolescence characteristics, family roles, and environment, (2) to study the relationship between the youths’ life skill level and their learning process. The research took place at Cikaret Village, South Bogor Sub-District. Sixty 60 respondents were involved. Data was gathered on September-November 2005, by interview and observation. Quantitative data were analyzed by Spearman-Rank correlation procedure. In this research, the youth’s life skills were correlated to their characteristic, to their family role, to their environment and learning process. Some important results of this research are: ( 1) the life skills were correlated with the learning process within the conditions of learning and the experimental learning, ( 2) the learning process of the adolescence were related to the family role, the environment role and the adolescence’s characteristics, and ( 3) improvement of the quality of the adolescence’s life skills were needed together with effort to increase their quality of life, including their family, environment and learning process.